Peran Kepemimpinan Kepala Madrasah dalam Pengembangan Kurikulum Merdeka di MTs. Negeri 2 Medan - Sri Andriani; Inom Nasution; Budi Budi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the implementation of the independent curriculum, the leadership role of the principal in developing the independent curriculum and supporting and inhibiting factors in developing the independent curriculum at MTs. Negeri 2 Medan. This research uses a qualitative research method with a phenomenological approach. The data collection process was carried out by means of observation, interviews and documentation. The informants in this research were the principal, the deputy principal for curriculum and several teachers. Based on the research results, the implementation of the independent curriculum in MTs. Negeri 2 Medan begins in the 2022/2023 academic year by teaching students to create projects in each subject and implementing the Strengthening Pancasila Student Profile Project (P5). In developing the independent curriculum, the principal plays the role of evaluator, supervisor and facilitator. The supporting factors in developing an independent curriculum at MTs. Negeri 2 Medan namely; the existence of adequate facilities and infrastructure, the competence and readiness of teachers and the leadershipIof the school principal. Meanwhile, the inhibiting factors in developing an independent curriculum at MTs. Negeri 2 Medan, namely; inadequate facilities and infrastructure, lack of competence and readiness of teachers and lack of cooperation between principal and teachers.